إضراب الأسرى والمعتقلين الفلسطينيين عن الطعام وقانون التغذية القسرية نظرة شرعية قانونية : (The Hunger-Strike of Palestinian Prisoners and Detainees and The Law of Force-Feeding: A Legal and Juristic View) - (Hani Rafeq Hamed Awad), هاني رفيق حامد عوض; (Bouhedda Ghalia), غالية بوهدة (At-Tajdid - Intellectual Refereed Journal, 2021)
Abstract The article deals with one of the most important issues of Palestinian prisoners and detainees in Israeli prisons and detention camps; that is the issue of hunger-strike. The hunger-strike is considered among the most successful means of obtaining rights and achieving demands and exposing to the international forums the cruelties of the Israeli occupation and their imposition of the law of force-feeding to Palestinian prisoners and detainees which by nature is unjust and against international conventions and norms from the legal perspective as well as from health and psychological aspects. The paper exposes the threats of force-feeding to the lives of the prisoners and detainees and describes the great danger which the prisoners and detainees are facing including the legal disadvantages and the painful means that force-feeding was administered. The study finds that the Palestinian prisoners did not chose hunger-strike until they have exhausted all the available peaceful means, but their demands were not fulfilled through mutual understandings and dialogues with the occupation regime. In this situation, hunger-strike was seen as the most powerful and useful option left despite its cruelty and difficulties in order to state their demands and rights. The research shows that the force-feeding through a plastic tube that enters through the nose while the prisoner is handcuffed to a chair so that he is not able to make any moves, as the tube reaches the stomach through the esophagus, or the food is injected directly to the veins. All these methods are against the laws and conventions of nations. Keywords: Prisoners, detainees, hunger-strike, force-feeding, Israeli prisons.